Implementation science in nutrition: Concepts and frameworks for an emerging field of science and practice - Tumilowicz, Allison; Ruel, Marie T.; Pelto, Gretchen; Pelletier, David; Monterrosa, Eva C.; Lapping, Karin; Kraemer, Klaus; De Regil, Luz Maria; Bergeron, Gilles; Arabi, Mandana; Neufeld, Lynnette; Sturke, Rachel (Oxford University Press, 2019)
Malnutrition in all its forms has risen on global and national agendas in recent years because of the recognition of its magnitude and its consequences for a wide range of human, social, and economic outcomes. Although the WHO, national governments, and other organizations have endorsed targets and identified appropriate policies, programs, and interventions, a major challenge lies in implementing these with the scale and quality needed to achieve population impact. This paper presents an approach to implementation science in nutrition (ISN) that builds upon concepts developed in other policy domains and addresses critical gaps in linking knowledge to effective action. ISN is defined here as an interdisciplinary body of theory, knowledge, frameworks, tools, and approaches whose purpose is to strengthen implementation quality and impact. It includes a wide range of methods and approaches to identify and address implementation bottlenecks; means to identify, evaluate, and scale up implementation innovations; and strategies to enhance the utilization of existing knowledge, tools, and frameworks based on the evolving science of implementation. The ISN framework recognizes that quality implementation requires alignment across 5 domains: the intervention, policy, or innovation being implemented; the implementing organization(s); the enabling environment of policies and stakeholders; the individuals, households, and communities of interest; and the strategies and decision processes used at various stages of the implementation process. The success of aligning these domains through implementation research requires a culture of inquiry, evaluation, learning, and response among program implementers; an action-oriented mission among the research partners; continuity of funding for implementation research; and resolving inherent tensions between program implementation and research. The Society for Implementation Science in Nutrition is a recently established membership society to advance the science and practice of nutrition implementation at various scales and in varied contexts.